Q-methodology to understand stakeholder discourses on bat conservation and management in view of the COVID-19 pandemic - Leong, Rachel; Lebarbenchon, Camille; Zhang, Jingru; Coleman, Joanna L. (Frontiers in Conservation Science, 2022)
Human-bat interactions are becoming more frequent with growing proximity between people and wildlife. As such, it is important to understand the perspectives of human stakeholders in these interactions, especially considering how media coverage of bats’ potential roles as the reservoirs of the ancestral virus to SARS-Cov2 has exacerbated negative perceptions of bats. We used Q-methodology to describe diverse viewpoints on bat conservation and management and identify areas of consensus among stakeholders in Singapore. We derived perspectives, problems, and priorities for bat conservation and management based on qualitative and quantitative analyses. The results reveal three distinct discourses. The ecocentric viewpoint advocates conserving bats for their intrinsic value. The anthropocentric viewpoint outright rejects the idea of conserving bats because of the perceived public-health threat that bats pose. The third discourse prioritizes educating citizens and enhancing general appreciation for biodiversity. All stakeholders agree on the need to reconsider COVID-19-related concerns about bats and address misconceptions that could hinder conservation. The top recommendation by stakeholders is to assess and improve bat-related attitudes and beliefs so that citizens become more supportive of conserving bats for their inherent value and roles in maintaining Singapore’s ecosystems. Considering both diverging and consensus viewpoints and engaging various stakeholders in conservation and management decisions can yield both attitudinal change and more effective solutions while meeting the ecological and social needs of conservation.